The Vascular Anatomy and Harvesting of the Lateral Femoral Condyle Flap in Pigs - Zuo, Yanhai; Xiao, Shouyun; Zhou, Xinchu; Yi, Lei (Journal of Reconstructive Microsurgery, 2024)
Clinically, there has been increasing employment of the lateral femoral condyle flap. The objective of this study was to explore the vascular anatomy of the lateral femoral condyle in pigs and to explore the feasibility of using pigs as an animal model of the lateral femoral condyle flap.A total of 20 fresh cadaveric hindlimbs of 4-week-old hybrid pigs were used in this study. The origination, course, and branches of the nourishing vessels of the lateral femoral condyle were observed in 15 specimens. The primary parameters included the variability in the anatomy of the vessels and the length and outer diameter of the vessels. Surgical procedures for the lateral femoral condyle flap were conducted on five specimens.The primary nourishing arteries of the lateral femoral condyle in pigs were the first superolateral geniculate artery, which was observed in all 15 specimens and had a diameter and length of 1.99 ± 0.44 mm and 2.27 ± 0.46 cm, respectively, as measured at their origination. The operation was performed in the lateral position. A 10-cm skin incision was made from the lower edge of the patella to the posterior lateral side of the distal femur. After blunt dissection of the intermuscular septum between the biceps femoris and vastus lateralis, the whole course of the first superolateral geniculate artery was exposed.The vascular anatomy of the lateral femoral condyle in pigs and that of humans exhibited great similarities. The harvesting of the lateral femoral condyle flap in pigs was as easy as that in humans. Pigs could serve as a suitable animal model for the lateral femoral condyle flap.
Keywords: animal model; flap; lateral femoral condyle; pig; surgery